Dynamics simulation of Vinyl Chloride Monomer (VCM) reactor using aspen hysys - Muhammad Nor Asnizan, Nawawi (2013)
The purpose of this research is to observe the dynamics simulation of Vinyl Chloride Monomer (VCM) process particularly in reaction section. The simulation is conducting by Aspen Hysys software by applied some steps. To develop dynamics simulation, the first step is developing steady state mode. Once the steady state simulation have completed, then sizing and installing the controller should be done. The third step is tuning of the controller. The characteristics of the reaction process can be investigated by changing of a raw materials flow rate. The result shows that the transient responses of the VCM reactor are inverse response process. The outcome result of this research is the oxychlorination reactor section of vinyl chloride monomer can be develop by using dynamics simulation as the monitoring process if any disturbances occur after the parameter is changed in process meanwhile the environment and safety of human secured from any pollution and dangerous incident. Apart from that, this study can become guidance to VCM industry to improve process performance. The significant of the study is improving knowledge of the characteristic of VCM process in reactor section by simulating process using dynamics simulation. Another significant is commercialization of dynamics simulation to VCM industries that bring 1001 benefit to industries.